Quantifying waste reduction and revenue saved based from converting food waste to liquid compost / Nurhusna Najwa Hussin - Nurhusna Najwa, Hussin (2018)
With escalating environmental issues, the need for a sustainable environment is becoming more necessary. In line with that, implementation of circular economy may be a good start towards becoming sustainable. A circular economy is an alternative to a traditional linear economy (make, use, dispose) in which we keep resources in use for as long as possible, extract the maximum value from them whilst in use, then recover and regenerate products and materials at the end of each service life. Majlis Bandaraya Petaling Jaya set up a Smart Waste Solution Lab at SS2 to make use circular economy in managing food waste. The aim of this study is to quantify waste reduction and revenue saved based from converting food waste to liquid compost. The objectives also include assessing public awareness on the importance of recycling household waste and hawker’s awareness on the importance of proper food waste management. The method involved were by distributing questionnaires to the public, hawkers and interviews were carried out with MBPJ operators at Smart Waste Solution Lab SS2 Petaling Jaya. The areas covered in the questionnaires and interviews were awareness on waste management, awareness on recycling activities, daily waste production, food waste handling, composting process, charges for landfilling process, operating cost and revenue information for composting process, energy and water consumption. The timeline for data collection was set for a period of six months that is from January to June 2018. At the end of sixth month, the results showed that a revenue was generated as a result of diverting food waste from landfill and reducing the number of dump truck trips to landfill site. This resulted in a saving approximately RM 10848.71. The revenue estimated for a year is RM 21697.42. Hence this savings could be use to start up other smart waste facility to encourage the implementation of circular economy throughout the nation. For public questionnaires, the results showed that more than 50% of respondents separate their food waste however awareness on composting food waste are still very low as 90% of them send their food waste to landfill. For hawker’s questionnaires, most of the food waste are coming from plate waste of customers and customers behavior whereas for morning market food waste are due to lack of adequate storage area. In the end of the questionnaires, most of the respondent agreed to contribute in composting food waste to liquid compost if incentive is given. With the savings achieved, MBPJ can demonstrate to other local city councils to duplicate this initiative as it not only saves money but most importantly saves the environment for the future.